MENINGKATKAN KEMAMPUAN MENGENAL WARNA MELALUI METODE EKSPERIMEN PADA ANAK USIA 3-4 TAHUN DI TK ARNI PUYUNG - ROKYAL HARJANTY (Lembaga Penelitian dan Pendidikan Mandala, 2018)
This study purpos, to improve the ability to recognize color through experimental methods in children age 3-4 years in TK ARNI Puyung. With the experimental method of direct involvement of children so that children gain direct experience in the learning process. This type of research is a collaborative classroom action research. Collaborative classroom action research that is researchers collaborating with class teachers in conducting research. This study uses a class action research model and points to the implementation process proposed by Miles and Huberman. The subjects in this study were children aged 3-4 years consisting of 8 girls and 6 boys. Data collection methods used are observation sheets (check list). The data analysis technique is done quantitatively. The results showed that the ability to recognize colors can be improved by the experimental method. As for the learning process, children are given the opportunity to experiment with colors that are simple and attractive to children. The results of the study increased gradually, this can be seen from the observational data on the Actions, Cycle I and Cycle II. The average percentage acquisition in before action is 49.41%, increased in Cycle I with a percentage of 63.69% and increased to 83.68% in Cycle II.